Locating the 'big hole' in HCI research - Reeves, Stuart (ACM, 2015)
In a recent Interactions article, “The Big Hole in HCI Research,” Vassilis Kostakos argued that HCI lacks persistent “motor themes,” based on a co-word analysis of keywords sections from the past 20 years of CHI papers. HCI as a discipline, it is argued, “simply roll[s] from topic to topic, year after year, without developing any of them substantially.”